2020
DOI: 10.1111/jpc.14702
|View full text |Cite
|
Sign up to set email alerts
|

Literature review on congenital glucose–galactose malabsorption from 2001 to 2019

Abstract: Aim: Congenital glucose-galactose malabsorption (CGGM) is a rare disease characterised by severe diarrhoea, dehydration and weight loss. To better understand CGGM, we investigated all the case reports and series of CGGM from 2001 to 2019. Methods: A review of reports of CGGM published from 2001 to 2019 was undertaken, using PubMed, Ovid Medline, Springer, Wanfang Database, CBMD database and CKNI database. The clinical features, diagnosis, treatment and prognosis of CGGM in these reports were obtained and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 29 publications
2
25
2
2
Order By: Relevance
“…Data are lacking regarding the incidence or prevalence of this disease. A recent review by Wang et al reported that out of 107 reviewed cases, 55 cases were from Saudi Arabia and Turkey, accounting for 78.2% of the total number of published cases [ 3 ]. Physicians should be vigilant in those countries when an infant presents with intractable, profuse watery diarrhea and dehydration along with failure to thrive that persist regardless of standard therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data are lacking regarding the incidence or prevalence of this disease. A recent review by Wang et al reported that out of 107 reviewed cases, 55 cases were from Saudi Arabia and Turkey, accounting for 78.2% of the total number of published cases [ 3 ]. Physicians should be vigilant in those countries when an infant presents with intractable, profuse watery diarrhea and dehydration along with failure to thrive that persist regardless of standard therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy infants, the intestinal sodium-dependent glucose cotransporter (SGLT1) drives glucose and water against their concentration gradients into enterocytes via Na+ and electrical gradients [ 2 ]. Mutations in SLC5A1 gene lead to a defect in SGLT1 across the intestinal brush border, which results in accumulation of unabsorbed sodium, glucose, and galactose inside the intestinal lumen [ 3 ]. GGM is characterized by neonatal onset of severe watery diarrhea that is fatal within few weeks without proper management [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTE is due to villous atrophy with crypt hyperplasia and focal crowding of surface enterocytes that resemble tufts, evidenced by histology of intestinal samples, total or partial villus atrophy, and crypt hyperplasia in the absence of inflammation, with the typical focal epithelial tufts that permit the differential diagnosis between MVID and CTE [15]. The diagnosis of GGM is based on a combination of tests that includes stool sugar analysis, hydrogen exhalation, and small bowel histology [26]. In patients with CCDs, molecular analysis may help define the therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of mutations in SGLT-1 are nonsense, frameshift or splice site, resulting in truncated proteins that are not expressed [ 79 ]. Missense mutations have been reported, which do not affect protein expression, but impair the transport ability of the protein [ 79 , 80 ]. Hypercalcaemia occurs in ~20% of cases and can be accompanied by nephrocalcinosis and elevated 1,25(OH) 2 D 3 [ 80 ].…”
Section: Low Serum Pthmentioning
confidence: 99%